On the dependence of response inhibition processes on sensory modality - Bodmer, Benjamin; Beste, Christian (Human brain mapping, 2017)
The ability to inhibit responses is a central sensorimotor function but only recently the importance of sensory processes for motor inhibition mechanisms went more into the research focus. In this regard it is elusive, whether there are differences between sensory modalities to trigger response inhibition processes. Due to functional neuroanatomical considerations strong differences may exist, for example, between the visual and the tactile modality. In the current study we examine what neurophysiological mechanisms as well as functional neuroanatomical networks are modulated during response inhibition. Therefore, a Go/NoGo-paradigm employing a novel combination of visual, tactile, and visuotactile stimuli was used. The data show that the tactile modality is more powerful than the visual modality to trigger response inhibition processes. However, the tactile modality loses its efficacy to trigger response inhibition processes when being combined with the visual modality. This may be due to competitive mechanisms leading to a suppression of certain sensory stimuli and the response selection level. Variations in sensory modalities specifically affected conflict monitoring processes during response inhibition by modulating activity in a frontal parietal network including the right inferior frontal gyrus, anterior cingulate cortex and the temporoparietal junction. Attentional selection processes are not modulated. The results suggest that the functional neuroanatomical networks involved in response inhibition critically depends on the nature of the sensory input. Hum Brain Mapp 38:1941-1951, 2017. © 2017 Wiley Periodicals, Inc.
Keywords: source localization; EEG; Electroencephalography; evokované potenciály; funkční lateralita; mladiství; Evoked Potentials; Brain Mapping; percepce; mužské pohlaví; elektroencefalografie; Functional Laterality; Adult; mladý dospělý; sensory modalities; inhibice (psychologie); rozhodování; Decision Making; Touch; Young Adult; mozková kůra; ženské pohlaví; Physical Stimulation; Reaction Time; Humans; reakční čas; mapování mozku; fyzikální stimulace; Cerebral Cortex; pozornost; Attention; parietal cortex; frontal cortex; Perception; response inhibition; dospělí; Female; Inhibition, Psychological; Adolescent; lidé; Male; hmat